Case Report: Neonatal Unexplained HUS Treated With Complement Inhibitor Eculizumab - Dorottya Kelen; Benedetta Chiodini; Valérie Godart; Brigitte Adams; Patrick Stordeur; Khalid Ismaili (Frontiers Media S.A., 2021)
Background: Hemolytic uremic syndrome (HUS) is rare in neonates. It is probably an under-recognized condition in the early postnatal period as it presents similarly to the most common perinatal asphyxia and to differentiate the two conditions is challenging. We describe the clinical presentation of a potential new subtype of neonatal HUS triggered by hypoxic-ischemic event. Our patient was successfully treated by a single dose of Eculizumab as early as at 9 days of life.Case Report: A 35-weeks infant was born with low hemoglobin and subsequently developed respiratory distress, hypotension, and acidosis. Blood transfusion was administered, acidosis corrected, neurological examination remained reassuring. Few hours later he developed renal failure, macroscopic hematuria, hemobilia, thrombocytopenia and coagulopathy refractory to platelet and fresh frozen plasma transfusions. No infection was found. Haptoglobin was non-measurable, and schistocytes present, complement factors C3, C4 and B were low, FBb increased. HUS was suspected. A single dose of Eculizumab™ was administered on day 9 of life. No genetic mutation of atypical HUS was found. He was discharged with improving renal function and developing cholestasis.Conclusion: In neonates with hemolytic anemia, thrombocytopenia, hematuria and renal failure, HUS should be suspected. In neonatal HUS Eculizumab should be considered as first-line therapy and discontinuation can be considered if no genetic mutation is found and clinical condition improves. In very young patients, cholestasis could appear as potential side effect of Eculizumab™.